Identifikasi Bakteri Bioaerosol di Laboratorium Mikrobiologi UIN Sunan Ampel Surabaya Menggunakan Analisis Gen 16S rRNA - Fadhillah, Ninik; Yuanita Rachmawati; Inggrit Tyautari; Muh. Ma’arif; Ade Syafira Fatau; Wifaqwudd Az-Zahra Rifti (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Bioaerosols are airborne particles containing living microorganisms or microbial fragments that can disperse in indoor environments. This study aimed to identify the morphological characteristics and community composition of airborne bacteria in three laboratories at UIN Sunan Ampel Surabaya using a combination of macroscopic and microscopic observations and 16S rRNA gene-based molecular analysis. Air samples were collected using the settle plate method and analyzed for spatial distribution, colony morphology, and taxonomic identification. Results showed variation in colony density among the laboratories, with Gram-positive bacteria (Staphylococcus and Bacillus) dominating at 71.4%, while Gram-negative bacteria (Pseudomonas and Moraxella) accounted for 28.6%. Molecular analysis confirmed species identification with sequence similarity ranging from 97.63% to 99.31%. These findings indicate that indoor bacterial communities are influenced by interactions between environmental sources and human activity. Proper ventilation management, surface hygiene, and biosafety procedures are essential to maintain air quality and minimize occupational health risks in laboratory settings.